2015
DOI: 10.1002/lno.10107
|View full text |Cite
|
Sign up to set email alerts
|

Photoadaptation to the polar night by phytoplankton in a permanently ice-covered Antarctic lake

Abstract: Photosynthetic microorganisms are a primary source of new organic carbon production in polar ecosystems. Despite their importance, relatively little is known about how they adapt to the bimodal solar cycles that exist at high latitudes. To understand how phytoplankton adapt to the extreme seasonal change in photoperiod, we transplanted cultures of a well‐studied laboratory model for photosynthetic cold adaptation, Chlamydomonas raudensis UWO241, back to the water column of Lake Bonney (McMurdo Dry Valleys, Ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 45 publications
1
38
0
Order By: Relevance
“…Following from work by Striegl et al (2001), a surge of recent research has confirmed that biogenic gases often accumulate over winter in seasonally frozen lakes (Ducharme-Riel et al 2015;Denfeld et al 2016) along with oxidized solutes including nitrate, sulfate, and carbonate/bicarbonate from methane oxidation (Gammons et al 2014;Hanson et al 2006;Powers et al 2017). These findings point to active benthic and planktonic communities (Bertilsson et al 2013;Hampton et al 2017) that affect whole-lake chemistry through sustained aerobic and anaerobic biological processes under ice-which may not be surprising given similar observations from permanently frozen lakes (Morgan-Kiss et al 2016;Powers and Hampton 2016).…”
Section: Introductionmentioning
confidence: 83%
“…Following from work by Striegl et al (2001), a surge of recent research has confirmed that biogenic gases often accumulate over winter in seasonally frozen lakes (Ducharme-Riel et al 2015;Denfeld et al 2016) along with oxidized solutes including nitrate, sulfate, and carbonate/bicarbonate from methane oxidation (Gammons et al 2014;Hanson et al 2006;Powers et al 2017). These findings point to active benthic and planktonic communities (Bertilsson et al 2013;Hampton et al 2017) that affect whole-lake chemistry through sustained aerobic and anaerobic biological processes under ice-which may not be surprising given similar observations from permanently frozen lakes (Morgan-Kiss et al 2016;Powers and Hampton 2016).…”
Section: Introductionmentioning
confidence: 83%
“…Consequently, little is known about the biogeochemical repercussions of ice formation on the liquid water columns in these systems. A recent synthesis of existing wintertime seasonally ice‐covered lake data revealed unexpectedly high concentrations of plankton and organic matter (OM) in the water columns (Hampton et al, ), a result also shown for permanently ice‐covered Antarctic lakes (Morgan‐Kiss et al, ), highlighting the gap in our understanding of biogeochemistry under lake ice. We also know that microbial activity mediates lake biogeochemical cycles, but the impacts of ice cover and ice cover formation on microbial communities are not well understood (Bertilsson et al, ; Safi et al, ).…”
Section: Introductionmentioning
confidence: 93%
“…The FRX, HOR, ELB and WLB lakes are hydraulically terminal (i.e., lacking outflows), whereas MIE has a seasonal outflow to the sea during periods of high water levels. The lakes receive continuous sunlight during the summer but no sunlight between mid-April and late September (Bowman et al, 2016;Morgan-Kiss et al, 2016). The geochemistries differ among these lakes; for one, they can be divided into three categories of salinity, with FRX being brackish, ELB and WLB hypersaline and MIE and HOR freshwater (Green and Lyons, 2009).…”
Section: Site Description and Sample Collectionmentioning
confidence: 99%